Managing Islamic Financial Planning Inclusion in Indonesia - Farikha Amilahaq; Provita Wijayanti; Brilian Citra Pertiwi (Institute for Research and Community Empowerment (LPPM TAZKIA), 2021)
Indonesia is a country with the largest Muslim population. However, the understanding of Islamic finance is still limited. Meanwhile, more people are becoming more aware of the importance of managing personal finances. The interest of Muslim community to financial planning is a great opportunity to improve Islamic financial inclusion. The community is not only learning how to control personal finance according to Islamic principles, but also knows how and where to invest funds in compliance to shariah principles. Long-term impacts can increase the share of the Islamic financial market in Indonesia, both in the Islamic banking sector, Islamic insurance, sukuk, Islamic capital market, or fintech. Thus the shariah ecosystem could be strengthened further. This paper surveys the literature in the area of Islamic financial planning, and aims to design the basic concepts of Islamic personal financial planning needs, as well as to compare it with conventional personal financial planning. The next stage is to calculate the factors that could increase the inclusion of Islamic personal financial planning. The output of this study is a conceptual framework of Islamic financial planning that could also improve Islamic financial literacy and inclusion.